Effective methods of using authentic materials in forming speaking competence (Ta'limning zamonaviy transformatsiyasi, 2024)
This topic explores the use of authentic materials, real-world texts, audio, and video, as a powerful tool for developing speaking competence in language learners. Furthermore, this topic also serves for knowing the various effective methods of utilizing authentic materials to enhance speaking competence in language learners. Keywords. Authentic materials, Speaking competence, Language learning, Second language acquisition, Communicative competence, Oral communication skills, Language instruction, Fluency and accuracy, Real-world materials, Interactional competence.